An interactive debugging tool for C++ based on dynamic slicing and dicing - Wichaipanitch, Winai; M. H., Samadzadeh (Frontiers in Engineering Innovation Research, 2003)
The main objective of this work was to develop an interactive debugging tool for C++ programs. The tool that was developed id called C++ debug and it uses program slicing and dicing techniques. The design started by including simple statements first and then expanded to pointers, structures, functions, and classes. In order for C++ debug to be more powerful , dynamic slicing rather than static slicing was chosen. The work includes new algorithms that handle Class, Function, and Pointer in C++. The results of this work are reported in two parts: PART I : Definitions and Algorithms, PART II : Implementation, Testing, and Evaluation. This is part II that reports on the overall design of C++Debug, some of its main implementation issues including its complexity, the testing of C++Debug, and its evaluation results.